2022
DOI: 10.3390/cryst12010096
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spinel-Hydroxyapatite Composite Utilizing Bovine Bone and Beverage Can

Abstract: Spinel-based hydroxyapatite composite (SHC) has been synthesized utilizing bovine bones as the source of the hydroxyapatite (HAp) and beverage cans as the aluminum (Al) source. The bovine bones were defatted and calcined in the air atmosphere to transform them into hydroxyapatite. The beverage cans were cut and milled to obtain fine Al powder and then sieved to obtain three different particle mesh size fractions: +100#, −140# + 170#, and −170#, or Al particle size of >150, 90–150, and <90 µm, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The detailed chemical reaction is discussed in Scheme 1. The lesser particle size within this range (>1 µm) may give a superior homogeneity of the distribution of particles, and superior bonding between the individual components of the composite, and it could increase the density of the composite (Oh et al, 1998;Pramono et al, 2022). Therefore, it is a critical factor that defines the composite's quality.…”
Section: Particle Size Analysismentioning
confidence: 99%
“…The detailed chemical reaction is discussed in Scheme 1. The lesser particle size within this range (>1 µm) may give a superior homogeneity of the distribution of particles, and superior bonding between the individual components of the composite, and it could increase the density of the composite (Oh et al, 1998;Pramono et al, 2022). Therefore, it is a critical factor that defines the composite's quality.…”
Section: Particle Size Analysismentioning
confidence: 99%
“…Pramono et al [15] have successfully synthesized hydroxyapatite composite with spinel fittings using bovine bones, beverage Al cans and Mg (as the only commercial reagent). It was shown that the decrease in Al particle size increases hardness and reduces the porosity of the novel perspective biocomposite material.…”
Section: Biomineralogymentioning
confidence: 99%
“…SIS is a simplification of Self-propagating high-temperature synthesis (SHS), where this process uses an exothermic reaction to initiate and maintain component combustion to produce the desired product. The SHS method can be applied to materials such as iron sand, titanium, carbon, and can also be applied to composite materials by aluminum and magnesium as a matrix or reinforcement [1][2][3]. The advantage of the SHS method is that the process uses high temperatures in order to obtain a very short time to reach the maximum combustion temperature due to the heat released during the exothermic reaction [4].…”
Section: Introductionmentioning
confidence: 99%